2016
DOI: 10.1136/oemed-2016-103606
|View full text |Cite
|
Sign up to set email alerts
|

Development of a job-task-exposure matrix to assess occupational exposure to disinfectants among US nurses

Abstract: Objectives Occupational exposure to disinfectants is associated with work-related asthma, especially in healthcare workers. However, little is known about the specific products involved. To evaluate disinfectant exposures, we designed job-exposure (JEM) and job-task-exposure (JTEM) matrices, which are thought to be less prone to differential misclassification bias than self-reported exposure. We then compared the three assessment methods: self-reported exposure, JEM, and JTEM. Methods Disinfectant use was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 38 publications
(77 reference statements)
0
45
0
Order By: Relevance
“…Information on general disinfection tasks (frequency of use of disinfectants to clean surfaces/medical instruments, use of spray) was collected in the occupational questionnaire [10, 21], as described previously [16]. These questions also were asked in the 2013 main questionnaire, i.e., before and independently of the 2014–2015 asthma sub-study (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Information on general disinfection tasks (frequency of use of disinfectants to clean surfaces/medical instruments, use of spray) was collected in the occupational questionnaire [10, 21], as described previously [16]. These questions also were asked in the 2013 main questionnaire, i.e., before and independently of the 2014–2015 asthma sub-study (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…In 2014, we initiated a case-control study on asthma nested within the NHSII, to study occupational determinants of asthma. In a recent publication, we address the challenge of assessing exposure to a wide range of disinfectants in this population, for which we developed a Job-Task-Exposure Matrix (JTEM) [16]. In the present paper, we investigated the association between occupational exposure to cleaning/disinfection tasks and specific agents, and asthma control.…”
Section: Introductionmentioning
confidence: 99%
“…Job-exposure matrices are also used to evaluate occupational exposure in large populations, but variability within jobs is not considered 12 23. Recently, a job-task-exposure matrix (JTEM) taking into account variability of exposure within jobs has been developed to evaluate exposure to seven disinfectants/spray, but may still be limited in assessing accurately individual exposure levels 24. The exposure assessment method presented in the current study has been designed to evaluate individual exposure levels, potentially in large populations, without relying on participants’ knowledge about their own exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, in a large study of US nurses,25 participants working in a hospital reported using mostly alcohol, hypochlorite bleach and quats (41%, 24% and 15%). In the same population, nurses were classified as highly exposed to alcohol, hypochlorite bleach or quats by a JTEM (41%, 34% and 48%) 24. High level of exposure to alcohol was also measured in five US hospitals15 and in one French hospital 14.…”
Section: Discussionmentioning
confidence: 99%
“…There has been increased use of job-exposure matrices (JEMs) to evaluate exposure, but this approach should be improved by adding new asthmagens and validating exposure by environmental sampling. A generic, as compared with specific, JEM may not capture exposure to some agents (e.g., latex), and a job–task–exposure matrix may be more appropriate (41). A large birth cohort study in the United Kingdom that used a JEM found that the population attributable fraction of lifetime occupational exposures for adult onset asthma by age 42 years was 16% (95% confidence interval = 3.8–22.0) (42).…”
Section: Methodsmentioning
confidence: 99%